Spatial dynamics and characterization of the ichthyoplankton community of natural and artificial reef environments on the coast of Paraná state, south Brazil - Boerseth, Cathrine (2016)
Artificial reefs (ARs) have been deployed on the inner shelf of Paraná State, south Brazil, to recuperate marine biodiversity and as protection against destructive trawling activities. The purpose of this study was to offer a first characterization of the ichthyoplankton community associated with the ARs and the adjacent archipelago of Currais. Two sampling methodologies were used; 1) plankton net attached to an underwater scooter and; 2) light-traps. A hydrodynamic model was used to study dispersal trajectories to and from the study area. Sampling was conducted between 31.07.14 and 04.04.16. A total of 13 families and 11 species were identified, expanding the total species list of the study area with six species and four families; 63% of fish larvae caught on the ARs were of reef associated species; abundance and species richness was higher on the ARs compared to samples taken at a distance from the ARs. First occurrence of the invasive muzzled blenny Omobranchus punctatus was registered. The hydrodynamic model provided insight on dispersal trajectories and connectivity. The results of this study can be used to better define guidelines for sustainable use of the ARs and the Currais archipelago, a Marine National Park since 2013.